The influence of virtual try-on and online customer reviews on purchasing decisions for Azarine cosmetics on Shopee with consumer trust as a mediating variable - Sartika, Aishvarya Hari Nurvindati; Suardana, Ida Bagus Raka (EDUCTUM: Journal Research, 2026)
This study aims to examine the influence of digital features, namely Virtual Try-On and Online Customer Review (OCR), on consumer trust and purchasing decisions for cosmetic products on the Shopee e-commerce platform. Using a quantitative approach with survey methods and statistical analysis, this study shows that Virtual Try-On significantly increases consumer trust, while its direct effect on purchasing decisions is not yet proven significant. OCR shows a very significant effect on trust, and trust positively mediates the effect of OCR on purchasing decisions. These results confirm that trust plays a crucial role in the consumer decision-making process, especially in the context of online shopping. These findings align with the Stimulus–Organism–Response (S-O-R) and Technology Acceptance Model (TAM) theoretical frameworks, which emphasize that digital experiences shape consumers' perceptions of trust and attitudes before ultimately deciding to purchase. Although the direct effect of both digital features is not yet statistically strong enough, their presence and role in building trust remain significant in driving purchasing decisions. The results provide an important contribution to the development of technology-based digital marketing strategies and emphasize the importance of increasing consumer trust through interactive features and customer reviews in enhancing the effectiveness of online promotions.